Epidemiology 2017
DOI: 10.1183/1393003.congress-2017.pa3506
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide association study of asthma and wheeze in childhood and adolescence

Abstract: Background: Asthma heritability has only been partially explained by genetic variants and is known to be sensitive to environmental factors, implicating epigenetic modifications such as DNA methylation in its pathogenesis. Methods: Using data collected in the Avon Longitudinal Study of Parents and Children (ALSPAC), we assessed associations of asthma and wheeze with DNA methylation at 7.5 and 16.5 years, at over 450,000 CpG sites in DNA from the peripheral blood of approx. 1000 participants. We used Mendelian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…Differences in study power and discovered methylation sites were also noted between the two studies, possibly due to differences in samples (peripheral blood mononuclear cells vs whole blood). 38 Reese et al also reported differential methylation in genes related to immune functions.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Differences in study power and discovered methylation sites were also noted between the two studies, possibly due to differences in samples (peripheral blood mononuclear cells vs whole blood). 38 Reese et al also reported differential methylation in genes related to immune functions.…”
Section: Discussionmentioning
confidence: 96%
“…Thirteen CpGs detected in Xu et al were replicated in the study by Reese et al (seven genome-wide significant, six nominally significant). 33 CpGs annotated to the IL5RA gene, a gene where differential methylation was first associated with asthma by Arathimos et al, were also replicated by Reese et al 33,38 We compared the available data from CpGs in three blood stud- 32,34 In blood studies, 41…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations